PARAGENESA MINERAL BIJIH SULFIDA HIDROTERMAL DI DAERAH KLUWIH KABUPATEN PACITAN JAWA TIMUR : PENDEKATAN BERDASARKAN MINERALOGI DAN INKLUSI FLUIDA - Sudarsono Sudarsono; I. Setiawan (Pusat Survei Geologi, 2012)
Hydrothermal activity in Kluwih, Tulakan Pacitan area East Java indicated by rock alteration zone, sulphide mineralization, and quatz vein NNE-SSW, NNW-SSE trend. Mineralization deposited at least in 6 stages, yaitu : 1st stage, pre mineralization deposited quatz (320°C), 2nd stage, deposited quartz + pyrite (290°C), 3rd stage, deposited quartz + pyrite + chalcopyrite + bornite ± galena ± sphalerite (260°C), 4th stage, deposited quartz + pyrite + cahalcopyrite + Tetrahedrite + bornite ± galena (220°C), 5th stage, deposited quartz + pyrite (200°C), and 6th stage or supergen stage, deposited secondary mineral (covellite, malachite, azurite) <100 °C. The hydrothermal system was able in Kluwih Pacitan and surrounding area interpreted as epithermal low suphidation system, or base metal horizon to precious metal horizon. Hydrothermal process initially by propilitic alteration and deposited of sulphides and quartz vein, then argilic alteration overprint both. Finally, surface erosion outcropted those deposits at surface.Key words : hydrothermal, mineralization, sulphide ore, Pacitan